Improving methods to measure critical thermal limits in phloem‐feeding pest insects. Issue 1 (11th March 2016) - Alford, Lucy; Burel, Françoise; van Baaren, Joan
Abstract: The ability to accurately assess thermal tolerance in the laboratory without compromising ecological relevance is essential to predict the impacts of global climate change on phytophagous pest insects such as the phloem‐feeding aphids. One method to study thermal tolerance employs a temperature‐controlled column to measure critical thermal limits. However, assessments are commonly made with little relation to the natural environment of the study species. This study measured critical thermal minima (CTmin ) for three cereal aphids – Sitobion avenae (Fabricius), Metopolophium dirhodum (Walker), and Rhopalosiphum padi (L.) (all Hemiptera: Aphididae) – in the absence and presence of host plant material to determine the best experimental design. Results revealed that CTmin measured in the presence of the host plant was significantly lower, suggesting that performing the measurement in the absence of the host plant could result in an underestimation of insect thermal tolerance. In addition, the study highlights the importance of understanding how an insect interacts with its environment, as this can reveal behavioural variation integral to differential survival at unfavourable temperatures.